Structural formation and thermal relaxation of quench-condensed Kr films: effect on EPR spectrum of trapped hydrogen atoms: Quantum Crystals - Dmitriev, Yu.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Hydrogen atoms were trapped in a quench condensed Kr matrix and investigated by EPR. Each hyperfinecomponent is a superposition of broad and narrow line. The spectrum of narrow lines shows an axial anisotropy of the hyperfine structure constant. The extent of the anisotropy is found to depend on both the deposition temperature, Tdep, and the temperature of the solid sample, Tsample. As Tdep increases, the broad lines diminish while the anisotropy of the spectrum of narrow lines becomes less pronounced. The spectrum of narrow lines originate from H atoms in well defined environments and is attributed to a superposition of two spectra given by the atoms in substitutional fcc and hcp sites. The spectrum of broad lines is assumed to originate from the atoms trapped in highly disordered regions in the lattice. These regions are found to start relaxingat Tsample as low as 12 K.